Mapping Far-right Chemical, Biological, Radiological, and Nuclear (CBRN) Terrorism Efforts in the West: Characteristics of Plots and Perpetrators for Future Threat Assessment. Issue 8 (16th November 2020) - Koehler, Daniel; Popella, Peter
ABSTRACT: The threat of chemical, biological, radiological and nuclear (CBRN) terrorism is widely attributed to collective actors based on a religious ideology, e.g. globally operating Salafi-jihadist groups like al-Qaeda or ISIL. Only limited attention has been given to the CBRN threat of violent domestic extremists in general or far-right terrorists specifically. Nevertheless, a number of incidents involving far-right activists and CBRN agents in Western countries are known to the public, even though these have had comparatively little impact on public threat perception. This study systematically collected public information about far-right CBRN incidents to identify their main characteristics. The authors were able to identify 31 incidents in Western countries since 1970, which display features contrary to generally assumed forms of CBRN terrorism. Far-right CBRN terrorism appears to be predominantly a lone-actor phenomenon oftentimes involving middle-aged and comparatively well-educated male perpetrators, mostly motivated by non-religious forms of far-right ideology (i.e. neo-Nazism, non-religious white supremacism) and indiscriminately targeting victims. Overall, far-right actors attempting to weaponize CBRN agents have been few and generally technically inept. However, the characteristics of the plots pose potential challenges for effective counter-measures and intervention, should the number of actors or the technical sophistication of plots increase in the future.